Production of adiponectin, an anti-inflammatory protein, in mesenteric adipose tissue in Crohn's disease. Issue 6 (11th May 2005) - Yamamoto, K; Kiyohara, T; Murayama, Y; Kihara, S; Okamoto, Y; Funahashi, T; Ito, T; Nezu, R; Tsutsui, S; Miyagawa, J-I; Tamura, S; Matsuzawa, Y; et al.
Abstract : Background and aims: A characteristic feature of Crohn's disease (CD) is mesenteric adipose tissue hypertrophy. Mesenteric adipocytes or specific proteins secreted by them may play a role in the pathogenesis of CD. We recently identified adiponectin as an adipocyte specific protein with anti-inflammatory properties. Here we report on expression of adiponectin in mesenteric adipose tissue of CD patients. Methods and results: Mesenteric adipose tissue specimens were obtained from patients with CD (n = 22), ulcerative colitis (UC) (n = 8) and, for controls, colon carcinoma patients (n = 28) who underwent intestinal resection. Adiponectin concentrations were determined by enzyme linked immunosorbent assay, and adiponectin mRNA levels were determined by real time quantitative reverse transcription-polymerase chain reaction. Tissue concentrations and release of adiponectin were significantly increased in hypertrophied mesenteric adipose tissue of CD patients compared with normal mesenteric adipose tissue of CD patients (p = 0.002, p = 0.040, respectively), UC patients (p = 0.002, p = 0.003), and controls (p<0.0001, p<0.0001). Adiponectin mRNA levels were significantly higher in hypertrophied mesenteric adipose tissue of CD patients than in paired normal mesenteric adipose tissue from the same subjects (p = 0.024). Adiponectin concentrations in hypertrophied mesenteric adipose tissue of CD patients with an internal fistula were significantly lower than those of CD patients without an internal fistula (p = 0.003). Conclusions: Our results suggest that adipocytes in hypertrophied mesenteric adipose tissue produce and secrete significant amounts of adiponectin, which could be involved in the regulation of intestinal inflammation associated with CD.